Tacrolimus dose modification in patients receiving concomitant isavuconazole after hematopoietic stem cell transplantation. (June 2021) - Trifilio, Steven; Rubin, Halina; Monacelli, Alexandra; Mehta, Jayesh
Introduction: Isavuconazole is increasingly being used for antifungal prophylaxis during stem cell transplantation. Isavuconazole is a moderate inhibitor of Cytochrome P4503A4, and tacrolimus levels are anticipated to be elevated when given concomitantly with isavuconazole. We developed and validated a dose-modified tacrolimus regimen to better achieve and maintain target tacrolimus levels. Methods : Allogeneic stem cell transplantation recipients who received concomitant tacrolimus and isavuconazole from September 2017 to September 2018 were included. Tacrolimus was adjusted to achieve a target range 8–12 ng/ml. Intravenous tacrolimus was first initiated at 0.02 mg/kg/day on day 1, and transitioned to oral therapy using a 2:1 conversion ratio ( n  = 48). Clinical observations showed high interpatient variability. The intravenous dose was then reduced to 0.017 mg/kg/day, and oral:intravenous conversion changed to 3.1:1 ( n  = 24). Results: Interpatient variability was high (lower in the 0.017 mg/kg/day group; P  < 0.0217). Patients in the 0.017 mg/kg/day group required fewer dose changes ( P  < 0.023) and had fewer levels >15 ng/ml ( P  < 0.021). Median tacrolimus dose declined over time; 0.016, 0.012 and 0.011 on days 1, 7 and 10 for patients receiving 0.02 mg/kg/day and 0.017, 0.014 and 0.013 in the 0.017 mg/kg group. Day 10 tacrolimus accumulation factor was 1.42 Rac(Cmax) in the 0.02 mg/kg/day cohort compared to 1.23 Rac(Cmax) in the 0.017 mg/kg/day cohort ( P  < 0.015). When transitioned to oral therapy, a oral:intravenous conversion ratio >3.1:1 was shown to improve chances for achieving target levels ( P  > 0.0744). Conclusion: We recommend initiating intravenous tacrolimus dose at 0.017 mg/kg/day and using a 3.1:1 oral:intravenous conversion to reduce interpatient variability, drug accumulation and the number of suboptimal tacrolimus levels. Tacrolimus requires frequent drug level monitoring.